2000
DOI: 10.1007/s11886-000-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Medical treatment of hypertrophic cardiomyopathy

Abstract: Current medical therapy of hypertrophic cardiomyopathy (HCM) is tailored to relieve symptoms of exercise intolerance, angina, or syncope. In recent years, new concepts in the pathophysiology of HCM have evolved. These concepts underlie our medical therapy and are discussed first in this review. Subsequently, the agents available for the medical treatment of HCM are discussed, along with a practical strategy for rapid medical reduction of outflow gradients. The mechanism of benefit of negative inotropes for obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The majority of patients have an abnormally thickened ventricular septum, which could lead to systolic anterior motion of the mitral valve and obstruction of the left ventricular outflow tract (LVOT) [ 1 ]. Initial pharmacological therapy including beta-blockers and verapamil produces a negative inotropic effect to relieve the obstruction [ 2 , 3 ]. In patients who are refractory to medical treatments, septal reduction therapy (SRT) is indicated.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients have an abnormally thickened ventricular septum, which could lead to systolic anterior motion of the mitral valve and obstruction of the left ventricular outflow tract (LVOT) [ 1 ]. Initial pharmacological therapy including beta-blockers and verapamil produces a negative inotropic effect to relieve the obstruction [ 2 , 3 ]. In patients who are refractory to medical treatments, septal reduction therapy (SRT) is indicated.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies with Ca^'-entry blockers indicate beneficial short-term effects on diastolic function, but only minor improvement after 6 month (considered to be long term in this study) [81]. Many studies focus on the reduction of the outflow tract obstruction, but it is questionable how important this is for symptoms and prognosis [81][82][83][84]-A retrospective study in the UK concluded improved survival in HCM children treated with high dose betaadrenoceptor blockers [83]. It has been shown that the outflow tract gradient can be reduced by left or biventricular pacing, septal alcohol injection or partial septal resection, with short term relieve of symptoms.…”
Section: Therapy In Hcmmentioning
confidence: 98%
“…Up to now two loci for JLNS have been identified. Homozygous and compound heterozygous mutations in both the KCNOl gene and KCNEl gene represent JLNSl and JLNS2 respectively [46,84,85]. In JLNS homozygous mutations (the human knock-out) or compound heterozygous mutations lead to complete loss of the functional cardiac potassium current 1^ explaining the severe cardio-auditory syndrome [45,46,86].…”
Section: -5 Mutations In Ion Channel Genes Are Causative For Cardiac Events In Lqtsmentioning
confidence: 99%